The Influence of the Social Bond on Self-control at the Moment of Decision: Testing Hirschi’s Redefinition of Self-control - Bouffard, Jeffrey A. (American journal of criminal justice, 2011)
Hirschi ( 2004 ) redefined self-control as the tendency to consider the “full range” of potential costs relevant to a criminal act, suggesting that such costs vary in number and salience based on one’s level of self-control. He also suggested self-control, as expressed at the moment of decision, was influenced by the individual’s level of social bonding; those with fewer bonds would exhibit less self control by considering fewer costs and finding them less salient when making a decision. This study presents an initial attempt to examine Hirschi’s theoretical statement linking concepts from the two theories. Presented with a hypothetical drunk driving scenario, participants were asked to identify perceived costs and salience as a measure of self-control, as Hirschi ( 2004 ) suggested. Results support Hirschi’s assertion demonstrating that the social bond impacts offending likelihood through its relationship to self-control expressed within the decision. Future theoretical and empirical directions are outlined.